Identification and Evaluation of Autoantibody to a Novel Tumor-Associated Antigen GNA11 as a Biomarker in Esophageal Squamous Cell Carcinoma - Wang, Huimin; Yang, Xiaoang; Sun, Guiying; Yang, Qian; Cui, Chi; Wang, Xiao; Ye, Hua; Dai, Liping; Shi, Jianxiang; Zhang, Jianying; Wang, Peng (Frontiers in Oncology, 2021)
The study aims to explore the diagnostic value of anti-GNA11 autoantibody in esophageal squamous cell carcinoma (ESCC) from multiple levels. Autoantibody against GNA11 with the highest diagnostic performance was screened out from the customized protein microarray. A total of 486 subjects including ESCC patients and matched normal controls were recruited in the verification and validation phases by using enzyme-linked immunosorbent assay (ELISA). Western blotting analysis was used to verify the ELISA results. Immunohistochemistry (IHC) was used to evaluate GNA11 expression in ESCC tissues and para-tumor tissues. In addition, a bioinformatic approach was adopted to investigate the mRNA expression of GNA11 in ESCC. Results indicated that the level of anti-GNA11 autoantibody in ESCC patients was significantly higher than that in normal controls and it can be used to distinguish ESCC patients from normal individuals in clinical subgroups (P<0.05), as revealed by both ELISA and western blotting. The receiver operating characteristic curve (ROC) analysis showed that anti-GNA11 autoantibody could distinguish ESCC patients from normal controls with an area under ROC (AUC) of 0.653, sensitivity of 10.96%, specificity of 98.63% in the verification cohort and with an AUC of 0.751, sensitivity of 38.24%, specificity of 88.82% in the validation cohort. IHC manifested that the expression of GNA11 can differentiate ESCC tissues with para-tumor tissues (P<0.05), but it can not be used to differentiate different pathological grades and clinical stages(P>0.05). The mRNA expression of GNA11 in ESCC patients and normal controls was different with a bioinformatic mining with TCGA and GTEx data in GEPIA. In summary, anti-GNA11 autoantibody has the potential to be a new serological marker in the diagnosis of ESCC.